Identification of a Novel Gammaherpesvirus in Canada lynx (Lynx canadensis) - Liam D. Hendrikse; Ankita Kambli; Caroline Kayko; Marta Canuti; Bruce Rodrigues; Brian Stevens; Jennifer Vashon; Andrew S. Lang; David B. Needle; Ryan M. Troyer (Viruses, 2019)
Gammaherpesviruses (GHVs) infect many animal species and are associated with lymphoproliferative disorders in some. Previously, we identified several novel GHVs in North American felids; however, a GHV had never been identified in Canada lynx (Lynx canadensis). We, therefore, hypothesized the existence of an unidentified GHV in lynx. Using degenerate nested and subsequently virus-specific PCR, we amplified and sequenced 3.4 kb of DNA from a novel GHV in lynx, which we named Lynx canadensis gammaherpesvirus 1 (LcaGHV1). Phylogenetic analysis determined that LcaGHV1 is a distinct GHV species belonging to the genus Percavirus. We then estimated the prevalence of LcaGHV1 in lynx by developing a PCR-based assay and detected LcaGHV1 DNA in 36% (95% CI: 22–53%) of lynx spleen DNA samples from Maine, USA and 17% (95% CI: 8–31%) from Newfoundland, Canada. The LcaGHV1 DNA sequences from Maine and Newfoundland lynx were nearly identical to each other (two nucleotide substitutions in 3.4 kb), suggesting that the unique lynx subspecies present on the island of Newfoundland (Lynx canadensis subsolanus) is infected with virus that very closely resembles virus found in mainland lynx. The potential ecologic and pathologic consequences of this novel virus for Canada lynx populations warrant further study.